2019
DOI: 10.12659/msm.916509
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Bispectral Index to Predict Recovery of Consciousness in Patients with Spontaneous Intracerebral Hemorrhage After Surgical Hematoma Evacuation: A Prospective Cohort Study

Abstract: Background Our study aimed to test the predictive value of the bispectral index (BIS) for the post-operational consciousness recovery in patients undergone hematoma evacuation due to spontaneous intracerebral hemorrhage (ICH). Material/Methods In this prospective cohort study, we enrolled adult spontaneous ICH patients after surgical hematoma evacuation who did not recover consciousness on the first postoperative day. After patient enrollment, the BIS was continuously m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…12,28 And finally, a lot of researchers have investigated the predictive performances of BIS scoring for neurological outcome or mortality in different clinical conditions such as after brain injury and other comatose patients in the last decades. 10,1517,21,29,30 Dou et al 10 found that BIS values >42.5 were correlated with the prognosis of comatose patients in ICU. Fabregas et al 16 studied a model relating BIS to the probability of recovery of consciousness in patients with severe brain injury.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…12,28 And finally, a lot of researchers have investigated the predictive performances of BIS scoring for neurological outcome or mortality in different clinical conditions such as after brain injury and other comatose patients in the last decades. 10,1517,21,29,30 Dou et al 10 found that BIS values >42.5 were correlated with the prognosis of comatose patients in ICU. Fabregas et al 16 studied a model relating BIS to the probability of recovery of consciousness in patients with severe brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the researchers investigated the predictive value of the BIS for the post-operational consciousness recovery and they showed that it might be a potential tool for predicting the consciousness recovery in intracerebral hemorrhage patients undergoing hematoma evacuation. 29…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations